Climate-change impacts on distribution, habitats, sustainability and cultivation planning of two economically and ecologically important forest trees (China fir and Masson pine) in China - Yanghui Zhao; Liang Xu; Ying Zhang; Yafeng Wen; Donglin Zhang (Global Ecology and Conservation)
Anthropogenic climate change (ANCC), which strongly affects forest trees, has brought major challenges. Unraveling the influences of ANCC on forest trees is essential for understanding the response of forests to climate change and devising future strategies for forestry construction and production. In this study, multi-species distribution models and ArcGIS were utilized to identify priority planting and tending areas and simulate the spatiotemporal variation of habitat suitability for two economically and ecologically important forest trees: China fir (Cunninghamia lanceolata (Lamb.) Hook.) and Masson pine (Pinus massoniana Lamb.) in China. Results showed that these two forest trees were significantly affected by precipitation and temperature. Currently, the priority planting and tending areas of China fir are mainly distributed in 169 and 261 counties, respectively, whereas the priority planting and tending regions of Masson pine are mainly distributed in 213 and 170 counties, respectively. The suitable habitats for the two forest trees will change significantly under four shared socioeconomic pathways (SSPs) in the future three periods (2050 s, 2070 s and 2090 s): (i) the transition zones between tropical and sub-tropical regions and between temperate and sub-tropical regions are the main expansion (Yunnan, Henan, Hubei and Anhui) and loss areas (Guangdong, Hainan, Hunan and Taiwan), respectively. (ii) the suitable habitat is facing a situation of “North expansion” and “South contraction” and moving northward as a whole with climate change. (iii) future hydrothermal change is the primary driver of the expansion, contraction and migration of the suitability habitats for both forest trees. Strengthening intergovernmental cooperation and increasing forest coverage to achieve carbon neutrality, as well as controlling and mitigating the rise in climate warming, will help address the challenges posed by climate change to forestry production and development.